Do leaves in Cyperoideae (Cyperaceae) have a multiple epidermis or a hypodermis? - Martins, Shirley [UNESP]; Pilatti, Vanesa; Vegetti, Abelardo; Scatena, Vera Lucia [UNESP] (Elsevier Gmbh, Urban & Fischer Verlag, 2012)
In Cyperaceae, leaf anatomical characters, in particular the presence of a hypodermis or of a multiple epidermis, have contributed in taxonomic and phylogenetic studies. In this family, the leaf epidermis is often described as uniseriate, and the cells of the subepidermal layers having no chloroplasts are treated as hypodermis. Both tissues have a different ontogenetic origin and hence are not homologous. The aim of the present work was to verify the origin of the subepidermal layers in eight species belonging to Cyperoideae. All species studied presented multiple epidermal layers that were confirmed by leaf ontogeny. In Fimbristylis complanata, F. dichotoma, Pycreus flavescens and P. polystachyos the mature leaves present multiple epidermal layers with cells of the distinct layers similar in shape and size: in the other species studied these cells are different. Especially in the latter case, a multiple epidermis is easily interpreted erroneously as a hypodermis, possibly leading to erroneous evolutionary conclusions. Making correctly distinction between a hypodermis and a multiple epidermis, and hence in case of doubt investigating the origin of the questioned tissue, is compulsory in order to use both characters in a phylogenetic context. Though in the past often called 'hypodermis', our leaf ontogenetical observations show that in all species studied, the subepidermical layers constitute a multiple epidermis, originating from the protodermis. (C) 2012 Elsevier GmbH. All rights reserved.
Keywords: Ontogeny; Leaf anatomy; Hypodermis; Multiple epidermis; Cyperaceae